Drought Monitoring during Growth Rangeland Coverage, Ardabil Province - saideh eiyni; saeide eini (تحقیقات کاربردی علوم جغرافیایی)
The aim of this research is to investigate drought stress in rangeland rangelands in Ardabil province. According to the monthly rainfall data, 4 synoptic stations of Ardebil province (Ardebil, Khalkhal, Meshgin Shahr and Parsabad Moghan) during the statistical period of 2016-1996 were used to calculate drought index (SEPI) index for 4 periods of 1, 3, 6 and 9 months. Landsat TM and OLI satellite imagery was also used to prepare landslide classification maps based on the maximum probability model and calculation of vegetation indices NDVI, EVI, SAVI and LAI. In order to investigate the relationship between the studied indices, Pearson correlation coefficient (R) and root mean square error (RMSE) have been used. The results of the classification showed that the extent of the rangelands of Ardebil province in 1394 in the year 1377, both in the rangeland and in the rangelands, is a significant decrease. According to the results of SPI, the drought condition during 2011-2015 is more than the other periods studied. Vegetation dispersal maps were based on decision tree tree classification algorithm and according to NDVI index for the studied months. Also, according to the results of the evaluation, the highest correlation was observed between the NDVI index and the 6-month SEPI index, and the lowest mean squared error was found between the SAVI index and the 6-month SEPI index, but in general, the most suitable indicator for Drought monitoring in Ardebil province pastures is a 6-month NDVI and SEPI indicator.